Report from the 3rd Cardiovascular Outcome Trial (CVOT) Summit of the Diabetes & Cardiovascular Disease (D&CVD) EASD Study Group - Schnell, Oliver; Standl, Eberhard; Catrinoiu, Doina; Genovese, Stefano; Lalic, Nebojsa; Lalic, Katarina; Skrha, Jan; Valensi, Paul; Ceriello, Antonio (Cardiovascular diabetology, 2018)
The 3rd Cardiovascular Outcome Trial Summit of the Diabetes & Cardiovascular Disease EASD Study Group was held on the 26-27 October 2017 in Munich. As in 2015 and 2016, this summit was organised in light of recently completed and published CVOTs on diabetes, aiming to serve as a reference meeting for in-depth discussions on the topic. Amongst others, the CVOTs EXSCEL, DEVOTE, the CANVAS program and the ACE-trial, which released primary outcome results in 2017, were discussed. Trial implications for diabetes management and recent perspectives of diabetologists, cardiologists, endocrinologists, nephrologists and general practitioners were highlighted. The clinical relevance of cardiovascular outcome trials and its implications regarding reimbursement were compared with real-world studies. The 4th Cardiovascular Outcome Trial Summit will be held in Munich 25-26 October 2018 ( http://www.dcvd.org ).
Keywords: biomedicínský výzkum; týmová péče o pacienty; kardiovaskulární nemoci; mezioborová komunikace; klinické zkoušky jako téma; Cooperative Behavior; Interdisciplinary Communication; kooperační chování; diabetes mellitus; Clinical Trials as Topic; lidé; Diabetes Mellitus; Cardiovascular Diseases; Biomedical Research; Patient Care Team; kardiologie; Cardiology; Humans